Can atrazine loaded nanocapsules reduce the toxic effects of this herbicide on the fish Prochilodus lineatus? A multibiomarker approach - Andrade, Laura Lui de; Pereira, Anderson Espirito Santo [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Martinez, Claudia Bueno dos Reis (Elsevier, 2019)
Atrazine (ATZ) is a widely used herbicide that has the potential to contaminate the environment and cause deleterious effects on non-target organisms. Release systems for ATZ have been developed to minimize this contamination, such as nanocapsules prepared with poly (ε-caprolactone) (PCL). The objective of this work was to investigate the effects of nanoencapsulated ATZ compared to ATZ on biomarkers of the freshwater teleost Prochilodus lineatus. The fish were exposed for 24 and 96 h to nanoencapsulated ATZ (nATZ) and atrazine (ATZ) at concentrations of 2 and 20 μg L-1, just to the PCL nanocapsules without the herbicide (NANO) in the corresponding amounts or only to dechlorinated water (CTR). The results showed that nATZ was less toxic compared to ATZ, as it did not promote an increase in glycemia, alterations in antioxidants, nor in carbonic anhydrase enzyme activity, and no increase in the frequency of micronuclei and other nuclear erythrocyte abnormalities either. However, exposure to nATZ, as well as to ATZ and PCL nanocapsules, resulted in a reduction in hemoglobin content, increase in erythrocyte DNA damage, as well as changes in Ca2+-ATPase activity, leading to a decrease in plasma Ca+2. The Integrated Biomarker Response Index (IBR) depicted that exposure to ATZ promoted changes in a greater number of biomarkers compared to nATZ, indicating that the nanoencapsulation of the herbicide protected the animal from the effects of ATZ
Keywords: Nanotechnology; Oxidative stress; Genotoxicity; Osmoregulation; Nanopesticide